Capital Structure, Profitability, and Market Value: Analysis of Tourism Issuers on the Indonesia Stock Exchange - Novi Azzahra (Athallah Publishing Globalindo, 2025)
Company value does not always increase every year. The increase and decrease in company value can be influenced by capital structure and financial performance. This study aims to determine the effect of capital structure and financial performance on company value in hotel, resort, and cruise line companies in the form of financial reports of companies listed on the IDX for the period 2018-2024. This study uses quantitative methods. This study uses secondary data taken from the official website of the Indonesia Stock Exchange (IDX), namely www.idx.co.id. The population of this research data is hotel, resort, and cruise line companies listed on the IDX for the period 2018-2024. This study has a population of 30 companies. The sample selection used a purposive sampling technique and obtained a sample of 11 companies. The analysis method used in this study is descriptive analysis, classical assumptions, multiple linear regression analysis, and hypothesis testing. The results of the analysis show that capital structure does not affect company value. Financial performance affects company value. Capital structure and financial performance do not affect company value.